VALIDITY AND EVIDENTIAL STRENGTH OF ELECTRONIC DOCUMENTS IN THE SETTLEMENT OF E-COMMERCE CIVIL 826 DISPUTES - Surizki Febrianto (Proceeding International Conference on Social Sciences, 2026)
Development of e-commerce transactions in Indonesia has driven the increasing use of electronic documents as evidence in civil dispute resolution. This study aims to analyze the validity and evidentiary power of electronic documents based on the national legal framework, specifically the Electronic Information and Transactions Law (UU ITE), the Government Regulation on the Implementation of Electronic Systems and Transactions (PP PSTE), and provisions of civil procedural law. This study also aims to identify practical obstacles faced by parties and law enforcement officials in authenticating digital evidence in court. The method used is normative legal research with a statutory and conceptual approach, supported by a literature review of relevant court decisions as well as civil law and information technology literature. The analysis was conducted qualitatively to evaluate the conformity between legal norms and evidentiary practices in court. Research findings indicate that electronic documents have legitimate standing as evidence as long as they meet the requirements of integrity, authenticity, and retrievability as stipulated in the ITE Law. However, their evidentiary strength depends heavily on the ability of the party submitting the evidence to prove the authenticity of the metadata, digital footprint, and the reliability of the electronic system used. The study also found that the lack of uniform national technical standards often hinders judges in assessing the evidentiary weight of electronic documents. Therefore, strengthening technical regulations and increasing the capacity of judicial officials to understand digital evidence is necessary.